2015
DOI: 10.4238/2015.july.27.14
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of cFLIP anti-apoptotic protein in the porcine corpus luteum and corpora albicans during the estrous cycle and pregnancy

Abstract: ABSTRACT. We determined expression and localization of the antiapoptotic cellular FLICE inhibitory protein (cFLIP) in the porcine corpora lutea (CL) and corpus albicans (CA) during estrous and pregnancy. The CL and CA were collected at different stages of estrous to determine cFLIP immunolocalization, and mRNA and protein expression. The mRNA expression of the short cFLIP isoform (cFLIP S ) was higher at the early and mid CL stages, and lower by the late CL stage (P < 0.01); mRNA expression of the long cFLIP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The mRNA expression levels of cFLIP S and cFLIP L were high during the pregnancy period, but there was no significant difference between cFLIP L during the estrous cycle and pregnancy. A recent study reported that high levels of cFLIP mRNA and protein were shown during the mid stages of the estrous cycle and pregnancy in porcine CLs [15]. The present study found significantly high levels of cFLIP mRNA and protein in CLs of Thai swamp buffalos during the early stage of the estrous cycle and during pregnancy (P < 0.05).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The mRNA expression levels of cFLIP S and cFLIP L were high during the pregnancy period, but there was no significant difference between cFLIP L during the estrous cycle and pregnancy. A recent study reported that high levels of cFLIP mRNA and protein were shown during the mid stages of the estrous cycle and pregnancy in porcine CLs [15]. The present study found significantly high levels of cFLIP mRNA and protein in CLs of Thai swamp buffalos during the early stage of the estrous cycle and during pregnancy (P < 0.05).…”
Section: Discussionsupporting
confidence: 62%
“…Apoptosis is a form of physiological cell death and has been demonstrated in luteal cells during luteolysis in cows [2][3][4], humans [5], sows [6], and rats [7]. It is well established that apoptosis is the dominant mechanism regulating apoptosis of granulosa [8][9][10] and luteal cells [2,[11][12][13][14][15]. Studies on apoptosis signal transduction have focused on cell death ligand-and receptor-dependent intracellular signaling.…”
mentioning
confidence: 99%
“…When luteolysis occurs, luteal cells exhibit a sort of spontaneous cell death called apoptosis (Sugino and okuda, 2007). It is well known that apoptosis is the major mechanism controlling luteolysis in luteal cells ( Jin et al, 2015).…”
mentioning
confidence: 99%